STRATEGI KOMUNIKASI PEMASARAN PADA THE TRANS RESORT BALI - Komang Alicia Trisnayanti; I Made Widiantara; Ni Ketut Suciani (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2026)
Tourism is one of the main pillars of the Bali regional economy that drives fierce competition in the hotel accommodation sector. Established in 2014 and located in a strategic and easily accessible area, The Trans Resort Bali positions itself with the positioning statement "A Leading Five-Star Resort for Business and Leisure". This study uses a qualitative case study approach that aims to identify the marketing communication strategies implemented by The Trans Resort Bali in improving the company's brand image and profitability. This analysis was conducted through the SWOT analysis method with data collection techniques in the form of interviews, observations, documentation and questionnaires filled out by the company. In the process of determining the weight and rating of internal and external factors that influence the marketing communication strategy, as many as 3 respondents participated in filling out the questionnaire. The results of this study indicate that the marketing communication strategy implemented is a marketing communication concept that includes advertising, sales promotions, direct marketing, digital marketing and social media as well as public relations. This strategy is expected to increase visibility, memorability and positive brand image among potential guests and customers to the profitability of The Trans Resort Bali. The company is located in Quadrant I (aggressive strategy) and Cell II (growth strategy) of the Internal-External Matrix, indicating that the hotel has significant internal strengths and various external opportunities that can be utilized to achieve business goals. This study also identified that the implementation of digital advertising, particularly on the Meta Ads and Google Ads platforms, is not optimal. Therefore, this study recommends several strategies, such as strengthening social media content, collaborating with influencers and travel bloggers, optimizing digital advertising, and organizing CSR (Corporate Social Responsibility) activities.